Farklı sagital ve vertikal iskeletsel ilişkilerin uyku ve hayat kalitesi üzerindeki etkilerinin araştırılması / Investigation of the effects of different sagittal and vertical skeletal patterns on the quality of life and sleep - YENİDÜNYA, DENİZ (My University, 2025)
Bu çalışma farklı sagital ve vertikal iskeletsel paternlerin uyku kalitesi ve ağız sağlığıyla ilişkili yaşam kalitesi üzerindeki olası etkilerini değerlendirmeyi amaçlamıştır. Çalışma grubu, Eylül 2022 ile Ekim 2023 tarihleri arasında Bezmialem Vakıf Üniversitesi Ortodonti Anabilim Dalı'na ortodontik tedavi için başvuran ve dahil edilme kriterlerini karşılayan hastalardan oluşmuştur. Dahil etme kriterleri arasında 18 yaşından büyük olmak, sefalometrik röntgen çekilmiş olmak, bireylerin anamnezinde psikiyatrik hastalık ya da obstrüktif uyku apnesi (OSA) olmaması ve kranyofasiyal sendrom olmaması yer almaktadır. Tüm hastaların restoratif tedavileri tamamlanmıştır ve periodontal sağlık durumları kontrol edilmiştir. Daha önce ortodontik/ortopedik tedavi gören hastalar çalışmaya dahil edilmemiştir. Toplamda 330 hasta dahil edilme kriterlerini karşıladı ve bilgilendirilmiş onamlarını aldıktan sonra aşağıdaki anketleri doldurarak çalışmaya katılmaları istendi: Beck Depresyon Ölçeği (BDÖ), Pittsburgh Uyku Kalitesi İndeksi (PUKİ) ve Ağız Sağlığı Etki Profili (OHIP-14). Anketi eksik doldurma ve Beck Depresyon ölçeğinde skoru 17 üzerinde olma ve beden kitle indeksi 30 üzerinde olma gibi dışlama kriterlerinden dolayı 50 hasta elenmiştir. Nihai örneklemde, 280 katılımcı sagital ve vertikal sefalometrik değerlerine ve GoGn ve SN hatlarına olan Hyoid mesafeleri dikkate alınarak kategorilere ayrılmıştır. Bu kategoriler arasında ağız sağlığına bağlı hayat kalitesi ve bileşenleri, uyku kalitesi ve bileşenleri karşılaştırılmıştır. Ayrıca grupların demografik verileri karşılaştırılmış ve iki anketin puanları arasında korelasyon varlığı araştırılmıştır. Sagital ve vertikal gruplar için PUKİ puanları karşılaştırıldığında, normodiverjan ve hiperdiverjan gruplar arasında sadece toplam puanlarda anlamlı fark gözlenmiştir. Hyoid, SN çizgisine yaklaştığında; "uyku bozukluğu" ve "gündüz işlev bozukluğu" arttıkça uyku kalitesinin azaldığı görülmüştür. Ağız sağlığına bağlı hayat kalitesinin vertikal ve sagital kraniyofasiyal paternlerle veya Hyoid-GoGn mesafesiyle ilişkili olmadığı bulunmuştur. OHIP-14-TR ile PUKİ arasında anlamlı bir korelasyon vardır. Bulgularımız farklı vertikal ve sagital iskeletsel paternlerin ağız sağlığına bağlı hayat kalitesi skorlarını etkilemediğini göstermiştir. PUKİ puanları sagital paternden etkilenmemiştir ancak vertikal patern dikkate alınarak oluşturulan gruplar arasında toplam puanda anlamlı farklılık dikkati çekmiştir. Bu farklılığa göre, uyku kalitesi hiperdiverjan bireylerde normodiverjanlara göre daha yüksektir.
This study aimed to assess the possible impact of different sagittal and vertical skeletal patterns on the sleep quality and the oral health related quality of life (OHRQoL). The study group consisted of the patients who applied for orthodontic treatment at Bezmialem Vakif University's Department of Orthodontics between September 2022 and October 2023 and who met the inclusion requirements. The inclusion criteria included being older than 18 years of age, having a cephalometric x-ray, having no reported psychiatric diseases, having no obstructive sleep apnea (OSA), and having no craniofacial syndrome. All the patients had their restorative treatments completed and they were checked for periodontal health status. The patients who had previous orthodontic/ orthopedic treatment were not included in the study. A total of 330 patients met the inclusion criteria were asked to participate in the study filling out the following questionnaires after obtaining their informed consent: Beck Depression Inventory (BDI), Pittsburgh Sleep Quality Index (PSQI), and Oral Health Impact Profile (OHIP-14). The demographic data including information such as gender, age, height, and weight was requested in the questionnaire. The following were the exclusion criteria: patients with a body mass index (BMI) of 30 or above, patients with missing questionnaire data, and patients who scored higher than the borderline clinical depression threshold on the depression screening instrument. According to exclusion criteria 50 patients were eliminated. In the final sample, 280 participants were classified according to their sagittal and vertical cephalometric values and the hyoid bone distances to the GoGn and SN lines. The ANB (A point-Nasion-B point) and the FMA (Frankfort Plane-Mandibular Plane) were measured on the cephalometric radiographs. The general score as well as the component scores determined by the Oral Health Impact Profile (OHIP-14 TR) and the Pittsburgh Sleep Quality Index (PSQI) questionnaires were compared between groups formed according to sagittal and vertical patterns and between groups formed related to the hyoid bone. In addition, the demographic data of the groups were compared, and the presence of correlation between the survey scores was examined. The final sample included 280 patients, 109 men and 171 women. There was no statistically significant difference among the groups considering the age parameter. Only the total scores of the normodivergent and hyperdivergent groups showed a significant difference when comparing the PSQI scores for the sagittal and vertical groups. It was observed that when the hyoid was closer to SN line; the sleep quality decreased with an increase in the "sleep disturbance" and "daytime dysfunction". OHRQoL was not found to be associated with vertical and sagittal patterns or Hyoid- xi GoGn distance. There was a weak and statistically significant correlation between OHIP-14 and PSQI. Our findings showed that various vertical and sagittal craniofacial features would not affect the OHRQoL scores. PSQI scores appear to be unaffected by the sagittal pattern, but a significant difference was noted in the total score between groups considering the vertical pattern.
Keywords: Diş Hekimliği = Dentistry